Interpretasi Penilaian Bahasa Indonesia Berbasis Digital - Tanjung, Tobi Bagustian; Hutagalung, Surya Masniari; Adisaputera, Abdurahman (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research uses a qualitative method based on a literature study to conclude theoretical concepts about certain concepts, as well as the methods, objectives, and types of interpretation of learning assessment. The assessment process, including the interpretation of student learning results, is better carried out through digital-based applications because it simplifies the process of administering assessment reports, drawing final conclusions, and reducing errors in the assessment process. Digital interpretation makes it easier for teachers to maintain objectivity in student learning outcomes and is part of digitalization, which must be introduced to students from an early age by teachers and schools.